CHARACTER EDUCATION AS REVEALED IN THE MOVIE FREEDOM WRITERS DIRECTED BY RICHARD LAGRAVENSE - Okclassiya Mega Sarajar; Mister Gidion Maru; Jenie Posumah (SoCul: International Journal of Research in Social Cultural Issues, 2021)
This research aimed to identify or found the value of character education revealed in the movie “Freedom Writers” directed by Richard Lagravense. This research uses a qualitative descriptive method and uses content analysis to analyze the data. The sources of data are taken from the movie “Freedom Writers” directed by Richard Lagravense and other documents such as journals, books, or articles related to the research from the analysis of the movie there is a value of honesty as a learning behavior in an effort to make someone trustworthy even in words, actions, and work. Tolerance refers to mutual respect for one another. The value of curiosity shows how they know more about something. The creative value is about having new ideas to achieve new things and the peace-loving value described attitudes and actions that are useful in social peace and mutual respect. The values ​​of honesty, tolerance, curiosity, creativity, and peace-loving are reflected in the students. Through the attitude of a teacher named Erin Gruwell, she can change the way students think from not looking at and gang violence, looking at religion, race, ethnicity, region border and looking at color differences because with her fortitude, she guides the characterless students to become a good character and want to achieve their future. It can be concluded that watching the movie “Freedom Writers” directed by Richard Lagravense can increase the character education of students.